Highly Defective Layered Double Perovskite Oxide for Efficient Energy Storage via Reversible Pseudocapacitive Oxygen-Anion Intercalation - Liu, Y.; Wang, Z.; Veder, Jean-Pierre; Xu, Z.; Zhong, Y.; Zhou, W.; Tade, Moses; Wang, Shaobin; Shao, Zongping (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim., 2018)
The use of perovskite materials as anion-based intercalation pseudocapacitor electrodes has received significant attention in recent years. Notably, these materials, characterized by high oxygen vacancy concentrations, do not require high surface areas to achieve a high energy storage capacity as a result of the bulk intercalation mechanism. This study reports that reduced PrBaMn 2 O 6- d (r-PBM), possessing a layered double perovskite structure, exhibits ultrahigh capacitance and functions as an excellent oxygen anion-intercalation-type electrode material for supercapacitors. Formation of the layered double perovskite structure, as facilitated by hydrogen treatment, is shown to significantly enhance the capacitance, with the resulting r-PBM material demonstrating a very high gravimetric capacitance of 1034.8 F g -1 and an excellent volumetric capacitance of ˜2535.3 F cm -3 at a current density of 1 A g -1 . The resultant formation of a double perovskite crystal oxide with a specific layered structure leads to the r-PBM with a substantially higher oxygen diffusion rate and oxygen vacancy concentration. These superior characteristics show immense promise for their application as oxygen anion-intercalation-type electrodes in pseudocapacitors.